Anglo-Irish architectural exchange in the early eighteenth-century : patrons, practitioners and pieds-à-terre - Hayes, Melanie (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2015)
This study sets out to bridge the gap between the formal architectural histories of London and Dublin in the early Georgian period, establishing the links between the vibrant architectural cultures of the two capital cities, at a significant time for the development of Dublin’s domestic architecture. Adopting a wide-ranging interdisciplinary approach, it weaves a rich array of contextual and circumstantial material around the skeletal frame work of the buildings, providing the connective tissue between the burgeoning architectural and material cultures of the two kingdoms. Formal connections are considered, specifically the links between the pioneering residential developments on the Gardiner estate in Dublin, at Henrietta Street (c.1725-50s) and to a lesser degree Sackville Street Upper (c.1750s), and the almost contemporary residential expansion in London’s West End, pointing up the debts to but also divergences from imported models, and the means by which they were transmitted. The figures who populate this study are of key concern, as agents in the dissemination of new architectural taste and conduits in the spread of architectural influence. Focusing on the people behind the development process, the architects, developers, builders and not the least the residents, this study seeks a fuller understanding of the cross-cultural experience of this close-knit group and the influential networks in which they operated, on both sides of the Irish Sea. In so doing, it offers new insights into the exchange of architectural taste between London and Dublin, the routes by which this took place, and the major protagonists involved.
Keywords: History of Art and Architecture, Ph.D.; Ph.D. Trinity College Dublin